Answer:
R = -3i + 4j + 12k
Step-by-step explanation:
Given that the displacement vector D is:
D = 3i - 4j
Substitute D in -4Dj to get the below vector
-4jD = -4j( 3i - 4j )
Using a cross product since the displacement are not parallel to each other
-4jD = (-4j × 3i) - ( -4j × 4j )
But j × I = - k while j × j = 0
-4jD = 12k
To find the displacement vector R,
Make R the subject of the formula in the equation below
D + R = 12k
(3i - 4j) + R = 12k
Use addition of vector
R = (- 3i + 4j + 0k) + ( 0i + 0j + 12k)
R = -3i + 4j + 12k